Comparison of (123)I-Metaiodobenzylguanidine (MIBG) and (131)I-MIBG Semi-Quantitative Scores in Predicting Survival in Patients With Stage 4 Neuroblastoma: A Report From the Children’s Oncology Group - Naranjo, Arlene (Pediatr Blood Cancer, 2011)
BACKGROUND: (123)I-metaiodobenzylguanidine (MIBG) scans are preferable to (131)I-MIBG for neuroblastoma imaging as they deliver less patient radiation yet have greater sensitivity in disease detection. Both (123)I-MIBG and (131)I-MIBG scans were used for disease assessments of neuroblastoma patients enrolled on Children’s Oncology Group (COG) high-risk study A3973. The hypothesis was that (123)I-MIBG and (131)I-MIBG scans were sufficiently similar for clinical purposes in terms of ability to predict survival. PROCEDURE: Patients enrolled on COG A3973 with stage 4 disease who completed (123)I-MIBG or (131)I-MIBG scans at diagnosis, post-induction, post-transplant, or post-biotherapy were analyzed. The performance of the Curie score for each MIBG scan type in predicting survival was evaluated. At each time point, survival curves for (123)I-MIBG versus (131)I-MIBG were compared using the log-rank test. RESULTS: Of the 413 patients on A3973 with at least one MIBG scan, 350 were stage 4. The 5-year event-free survival (EFS) and overall survival (OS) rates were 33.4 ± 3.6% and 45.6 ± 4.0% (N = 350). At post-induction, EFS (P = 0.3501) and OS (P = 0.5337) for (123)I-MIBG versus (131)I-MIBG were not significantly different. Similarly, comparisons at the three other time points were non-significant. CONCLUSIONS: We found no evidence of a statistically significant difference in outcome by type of scan. For future survival analyses of MIBG Curie scores, (123)I-MIBG and (131)I-MIBG results may be combined and analyzed overall, without adjustment for scan type.